Core Stability Exercise For Low Back Pain: A Literature Review - Afriannisyah, Entan; Herawati, Lucky; Widyawati, Melyana Nurul (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Back pain is a major health problem in the world. This back pain is experienced by athletes, pregnant women of late trimester pregnancy and postpartum mothers. So far, back pain can be treated using chemical drugs which have side effects on the body. Physical activity is an alternative option to help with back pain. Core stability exercise is a non-pharmacological method that can relieve back pain symptoms in sufferers. This literature review aims to analyze the benefits of core stability exercise in patients with low back pain. The research method used by the author is a literature review using databases through Pubmed, Science Direct, and Google Scholar from 2008 to 2019 This article discusses core stability exercises in people with low back pain. The results of the literature search show that core stability exercise can reduce low back pain.